Does Insurance Status Affect Access to Care Among Ankle Fracture Patients? An Institutional Retrospective Study. Issue 4 (16th October 2019) - McKissack, Haley; He, Jun Kit; Moraes, Leonardo V. M.; Anderson, Matthew; Wislon, John T.; Viner, Gean C.; Jha, Aaradhana J.; Mcmurtrie, James T.; Shah, Ashish B.; Naranje, Sameer M.
Category: Ankle, Trauma Introduction/Purpose: Ankle fractures are urgent, and often emergent injuries which require immediate evaluation and treatment. Delayed access to care may subject the patient to increased risk of complications, particularly if surgical management is warranted. Medicaid is a state and federal insurance program in place for those with low income, which has previously been associated with delayed access to care among patients with ACL tears and total hip arthroplasties. Studies have also shown delayed access to care among ankle fracture patients; however these studies have used hypothetical patients rather than existing data regarding timeliness of care. The purpose of this study is to assess whether patient insurance status affects access to care using data from a single institution. Methods: Patients who underwent open reduction and internal fixation for an ankle fracture between the years 2008 and 2018 at a single institution were identified by CPT codes 27829, 27784, 27822, 27814, 27769, 27792, and 27766. Patients who had polytraumatic injuries, open injuries, Medicare, no insurance, indigent/charity insurance, self-pay, or whose insurance information was not available were excluded. Insurance status was retrospectively identified as well as date of injury, date of first visit to the institution's hospital for the injury, and date of surgery. Time elapsed from date of injury to date of surgery, date of injury to date of first visit, and date of first visit to date of surgery was compared between patients with private insurance and Medicare. P-values of less than 0.05 were considered statistically significant. Results: Results showed statistically significant differences in mean time from injury to first appointment and mean time from injury to surgery between patients enrolled in Medicaid and those with private insurance. Average time from injury to first appointment was 3.1 days and 6.6 days for privately-insured patients and Medicaid patients, respectively (p<0.0001). Average time from injury to surgery was 8.1 days for patients with private insurance, and 12.7 days for patients enrolled in Medicaid (p<0.0001). Conclusion: Patients who are enrolled in Medicaid have significantly delayed access to care as compared to those who have private insurance. For ankle fracture patients this is a critical healing time, and delayed care may result in increased costs, increased utilization of healthcare resources, higher complication rates, and poorer patient outcomes. Therefore, it is important that the orthopaedic community continues to progress toward improvising and expanding access to care for all patients.